“Det känns som att jag hela tiden måste kämpa för mina rättigheter” : Barndomsdöva personers erfarenheter av kontakt med myndigheter - Lundgren,Vicky; Wedding,Klara (2018)
The aim of this study was to examine and illuminate how people who are born deaf experience their encounters with administrative authorities. The study was based on qualitative interviews. Several themes were identified in the interviews: knowledge, deaf competence, accessibility, communication, interpreter usage, audism and discrimination. The analysis was based on the notions of accessibility, stigma, power, redistribution and recognition. We found that the knowledge and understanding of deaf persons, deafness, deaf culture and the deaf community need improvement, both in general society and in occupations where meeting different people is essential, as this lack of understanding may result in audism and stigma. Based on the interviews, the accessibility for deaf persons in administrative authorities proves to be deficient. We found that one way to improve the accessibility is by using redistribution of material resources, by using resources that are already available as for example videophone for communication. But the knowledge of these resources is lacking. Our result also showed the importance of an interpreter, to enable deaf persons to receive adequate information and express themselves in their first language (sign language). As a conclusion, even though the view on deafness has substantially improved historically, there is still a great need for further improvement.
Keywords: deaf; deaf competence; administrative authorities; accessibility; discrimination